2012
DOI: 10.1080/14681994.2012.660141
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and research concerns with vibratory stimulation: a review and pilot study of common stimulation devices

Abstract: The parameters of vibrators used for sexual stimulation in laboratory settings and therapeutic contexts are usually unknown. The unidentified range of vibrator characteristics commonly used for sexual stimulation would help identify appropriate vibrator for different purposes and clients. Seven vibrators used for sexual stimulation were tested using a piezoelectric accelerometer mounted on their housing to quantify frequency, displacement, and acceleration of each. Vibratory frequency ranged from 43 to 148 Hz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…The vibrator is placed on areas self-reported to best provoke the sexual response in men (under the penile glans, [99]) and women (over the clitoral hood [100]). Commercial genital stimulation devices vary widely in their motor characteristics, and testing pointed to the selection of higher displacement devices for research purposes [101]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vibrator is placed on areas self-reported to best provoke the sexual response in men (under the penile glans, [99]) and women (over the clitoral hood [100]). Commercial genital stimulation devices vary widely in their motor characteristics, and testing pointed to the selection of higher displacement devices for research purposes [101]. …”
Section: Methodsmentioning
confidence: 99%
“…This was binned into 9 equal setting to allow quantification of the intensity. At a setting of “1” no vibration was occurring; at a setting of “9” the maximum setting on the device [101] was used. Maximum stimulation included oscillations at 110 Hz with 40 μm displacement.…”
Section: Methodsmentioning
confidence: 99%
“…Vibrators as a sexual stimulus in research are not often used for women despite their relative widespread use as a tool to enhance sexual arousal in personal settings [53]. Vibrators consist of a vibrating motor that is encased in a housing and applied to the genital area as a means of sexual stimulation (for detailed description of vibrator properties, see [54]). Research using vibrators has demonstrated that vibrotactile stimulation can produce significantly greater genital responses, as measured through VPP, when paired with film clips than film clips alone [52].…”
Section: Methodsmentioning
confidence: 99%
“…Research using vibrators has demonstrated that vibrotactile stimulation can produce significantly greater genital responses, as measured through VPP, when paired with film clips than film clips alone [52]. A recent study examining the technical properties of various vibrators suggests that vibrator use can provide a more controlled stimulus intensity than other modalities, although the authors do point out that most studies using vibrotactile stimulation to date have provided very little technical information or standardization of vibrator use between participants [54]. The few recent studies that have used vibrotactile stimulation have demonstrated increases in genital response with vibrator use [55–59]; however, the use of a vibrator may interfere with concurrent genital arousal recording for devices that require physical contact with participants, such as VPP, as the vibrator might produce movement artifacts in the data recording.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation